The Federal Democratic Republic of Ethiopia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2005)
This Selected Issues paper assesses the implications of a significant increase in the flow of external financing and grants on real GDP growth in Ethiopia. The paper presents an analysis of the sources of growth during 1991/92-2003/04, as well as an assessment of potential GDP growth. The paper also seeks to assess the historical relationship between foreign aid and the performance of the external sector in Ethiopia to establish whether foreign aid inflows have had an adverse effect on the tradable goods sector in the past.